USAHA PENGAWAS DAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU PAI DI MADRASAH KOTA SOLOK - Sarasasti Sarasasti (al-fikrah: Jurnal Manajemen Pendidikan, 2016)
This research concerned on the role of the supervisor and headmaster as an educational consultant for teachers to improve the quality of education. The teachers’ job performance can be known from their ability to plan, implement, evaluate and follow up the instructional activities. This research was descriptive qualitative by using interview and documentation as instruments. The results found that there were 7 programs applied to improve the teachers’ job performance 1) training teachers’ responsibility; 2) training teachers’ on instructional implementation; 3) training teachers on instructional evaluation; 4) training teachers’ discipline; 5) training teachers’ commitment; 6) training teachers’ loyalty; and 7) training teachers’ motivation. The way the supervisor and headmaster improve the teachers’ job performance by giving proportional DP3 score, and they wish to improve the teachers’ job performance because there is program of training teachers’ responsibility. Keywords:  Efforts, Supervisor, Headmaster, Teacher’s Job Performance